S Sistem Informasi PO Sudiro Tungga Jaya Berbasis Web: Studi Kasus di Terminal Magetan - Bagus Yudo Nugroho (JURNAL PILAR TEKNOLOGI Jurnal Ilmiah Ilmu Ilmu Teknik, 2025)
Bus fleet management is a crucial part of bus company (PO) operations, ensuring efficient, timely, and organized travel. Currently, the bus scheduling and ticket reservation process at PO. Sudiro Tungga Jaya is still done manually, often leading to problems such as delays in information and schedule recording errors. To address these issues, a scheduling and ticketing system was developed at PO. Sudiro Tungga Jaya. This system was built and designed using the waterfall method and tested using black box testing. This system is expected to assist management in managing fleet operational schedules more effectively and efficiently and facilitate passenger ticket reservations. Test results for PO. Sudiro Tungga Jaya's web-based scheduling information system achieved the expected results, achieving a 100% system success rate.